2017
DOI: 10.1063/1.4983089
|View full text |Cite
|
Sign up to set email alerts
|

Giant perpendicular exchange bias with antiferromagnetic MnN

Abstract: We investigated an out-of-plane exchange bias system that is based on the antiferromagnet MnN. Polycrystalline, highly textured film stacks of Ta / MnN / CoFeB / MgO / Ta were grown on SiO x by (reactive) magnetron sputtering and studied by x-ray diffraction and Kerr magnetometry. Nontrivial modifications of the exchange bias and the perpendicular magnetic anisotropy were observed both as functions of film thicknesses as well as field cooling temperatures. In optimized film stacks, a giant perpendicular exchan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…However, the spin orientation is controversial and might depend critically on the lattice constants. In previous studies, some of the authors of this article have shown its utility for exchange bias applications with large exchange bias fields at room temperature [22][23][24][25][26][27]. However, the critical thickness for the onset of exchange bias was observed to be around 10 nm at room temperature, leading to the conclusion that MnN has a small magnetocrystalline anisotropy energy density [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the spin orientation is controversial and might depend critically on the lattice constants. In previous studies, some of the authors of this article have shown its utility for exchange bias applications with large exchange bias fields at room temperature [22][23][24][25][26][27]. However, the critical thickness for the onset of exchange bias was observed to be around 10 nm at room temperature, leading to the conclusion that MnN has a small magnetocrystalline anisotropy energy density [22].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the possibility of achieving a large out-of-plane loop shift using MnN is of great interest. Zilske et al [23] reported a giant perpendicular exchange bias of 3.6 kOe at room temperature in MnN/CoFeB bilayers. The samples had a similar composition and identical deposition conditions to some of the in-plane samples described earlier.…”
Section: Exchange Bias: Out-of-plane Studiesmentioning
confidence: 99%
“…Для ультратонкого тонкого слоя CoFeB толщиной 0.65 нм в системе MnN / CoFeB / MgO / TA может быть достигнуто значение h EB = 3600 Э [24].…”
Section: заключениеunclassified